Leptin levels in gingival crevicular fluid during canine retraction: in vivo comparative study. (March 2019) - Sar, Sanjit Kumar; Shetty, Divya; Kumar, Piush; Juneja, Saurabh; Sharma, Payal
Objective: To evaluate and compare the leptin levels in gingival crevicular fluid (GCF) and rate of canine retraction using an elastomeric chain and nickel–titanium (NiTi) closed coil spring. Design: In vivo, clinical study. Setting: Orthodontic department at ITS Centre for Dental Studies and Research, Ghaziabad, India. Participants: Twenty-seven patients reported to the Department of Orthodontics at ITS Centre for Dental Studies and Research. Methods: Twenty-seven patients were included in the study in which canine retraction was carried out with an elastomeric chain and NiTi closed coil spring on either side of the arch applying 150 g of force on both sides. GCF samples were collected before the commencement of canine retraction, on the first, seventh and 21st day after application of force and were analysed for leptin levels by the ELISA technique. Impressions for the study model were taken at baseline and after 21 days to measure the rate of tooth movement bilaterally with an electronic digital calliper. Results: The results obtained within both groups showed a significant decrease in leptin levels from baseline to 21 days ( P = 0.0001). There was no significant difference in leptin levels between both groups, but leptin levels decreased more in the NiTi closed coil spring group. The rate of tooth movement is not significantly different between both groups, but space closure is faster in the NiTi closed coil spring group. Conclusions: Leptin levels in GCF showed a significant decrease during canine retraction using an elastomeric chain and NiTi coil spring; there was no significant difference in the rate of tooth movement between both the groups.